2022
DOI: 10.1080/21645515.2022.2090176
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of inactivated COVID-19 vaccination in adult rheumatic patients in South China: a prospective study

Abstract: Patients with rheumatic diseases (RD) are considered to be a high-risk population for infection with the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). The effectiveness of inactivated COVID-19 vaccinations (ICVs) was described as more effective than 95%. Despite this, no data on the immunogenicity and safety of the ICV in Han race stable RD patients in China. In this study, we sought to assess the safety and immunogenicity of the ICVs in RD patients in South China. A total of 80 adult stable RD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Furthermore, they also found that the risk of COVID-19 infection in the Chinese population was low within 3 months following immunization, but that the protective effect of the vaccine would be weakened after 3 months. 4,14 Both the Korean College of Rheumatology and the American College of Rheumatology advise immunization for patients with RMDs. Regretfully, guidelines mostly concentrate on mRNA and adenovirus vaccines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they also found that the risk of COVID-19 infection in the Chinese population was low within 3 months following immunization, but that the protective effect of the vaccine would be weakened after 3 months. 4,14 Both the Korean College of Rheumatology and the American College of Rheumatology advise immunization for patients with RMDs. Regretfully, guidelines mostly concentrate on mRNA and adenovirus vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…2 On the one hand, since immunosuppressive medications could lessen the immunogenicity of vaccines, patients might not have sufficient immune defenses. [3][4][5] On the other hand, patients worried that immunizations would disturb the delicate immunological homeostasis and worsen the underlying RMDs. 6,7 Currently, mRNA and adenovirus vaccines are the primary topics of study on COVID-19 vaccination of RMD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the need for prophylactic vaccination with safety and efficacy is paramount to mitigate the severity of the disease ( 41 , 66 ). The commercially available vaccine included messenger RNA (mRNA) vaccine encoding the spike protein ( 67 ), adenovirus-based vaccine ( 68 ), and inactivated COVID-19 vaccination ( 69 ). Laboratory and clinical investigations were still accelerated to identify a new vaccine against SARS-CoV-2 virus variants ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory and clinical investigations were still accelerated to identify a new vaccine against SARS-CoV-2 virus variants ( 22 ). The effectiveness of two doses of mRNA vaccine against SARS-CoV-2 was 90–92% ( 70 ), while the effectiveness of the inactivated vaccine was more than 95% ( 69 ). As the vaccination effectively protected persons from being infected, long-term COVID-19 involving PCF was diminished ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the availability of vaccines, COVID‐19 vaccination rates in Asian countries, including China, remain low (27). Other than the messenger RNA and adenovirus vector vaccines used in western countries, inactivated COVID‐19 vaccines were widely used in China.…”
Section: Introductionmentioning
confidence: 99%